PENGARUH DONGENG DAN KEMAMPUAN KOMUNIKASI TERHADAP KEMAMPUAN BERCERITA SISWA KELAS II SD BEKASI UTARA - ARDINI, PUPUNG PUSPA (JURNAL PENDIDIKAN ANAK USIA DINI, 2012)
This research is done in order to find out the influence between folk tale and communication ability to the story telling ability of 2nd grade student in Bekasi. Based on the analysis of data,thus it can be concluded that (1) story telling ability student that is given modern fantasy tale is higher than story telling ability that is given traditional folk tale, (2) there is interaction between folk tale with communication ability through story telling ability 2nd grade students, (3) story telling ability student that have higher communication and given modern fantasy tale is higher than a group of student that is given traditional folk tale, (4) story telling ability student that have lower communication and given modern fantasi tale is same with a group of student that is given traditional folk tale. From some of the research findings implies (1) efforts of teachers in determining the method of developing the ability to tell the studentsin 2nd grade, (2) selection of tales for students which is suitable for their age and mail stone, (3) folk tales interaction and communication ability through story telling ability 2nd grade students.Keywords: taleâs communication skills, ability to tell